What role does instructional quality play for elementary school children’s science competence?: A focus on students at risk = Zur Bedeutung von Unterrichtsqualität für die naturwissenschaftliche Kompetenz von Grundschulkindern : ein Fokus auf Kinder mit ungünstigen Lernvoraussetzungen - Decristan, Jasmin; Kunter, Mareike; Fauth, Benjamin; Büttner, Gerhard; Hardy, Ilonca; Hertel, Silke (Journal for educational research online, 2016)
Research on classroom instruction has consistently identified characteristics that contribute to student learning. For instance, these include structural-organizational aspects (e.g., classroom management) and affective aspects (e.g., classroom social climate). The idea that the effects of instruction may differentially depend on students’ characteristics has been investigated within the scope of aptitude-treatment-interactions (ATI) research. This study of elementary school (1,041 students, 54 classes) builds on ATI and examines main effects and interaction effects of instructional quality (i.e., classroom management and classroom social climate) and individual risks of school failure (i.e., demographic risk: immigration background or functional risk: low cognitive ability scores) on students’ science competence. Based on hierarchical linear modeling and class-level aggregated student ratings of instructional quality, results show a positive link between classroom social climate and science competence but not for classroom management and science competence. As its most important finding, our study demonstrates the compensatory capacity of instructional quality to narrow the achievement gap between students at risk and their peers. Furthermore, classroom management also counteracted risk of school failure when controlling for students’ language proficiency.